HUBUNGAN TUGAS KELUARGA DENGAN KEJADIAN TB PARU DI WILAYAH KERJA PUSKESMAS PERUMNAS II PONTIANAK TAHUN 2014 - ., Vicky Dian Febriani (Universitas Tanjungpura, 2014)
Background: The magnitude of the incidence of TB each year in the city of Pontianak requires families to be moresensitive to the health problems that can be solved if the family can carry out their duties properly.Aims: This study aims to analyze the relationship between family duties with pulmonary TB incidence inPuskesmas Perumnas II Pontianak in 2014.Methods: This study used a cross-sectional study design descriptive analitic approach. The statistical test used isthe Chi-Square. The samples were families who have family members who have pulmonary TB disease. Samplingtechnique of this study is the total sampling with 65 respondent.Results: The task of the family in identifying health problems with good categories is 60%, to decide theappropriate action for the health of family members who suffer from pulmonary tuberculosis by good category is89.2%, caring for family members who suffer from pulmonary tuberculosis with good category is 60%, creatingand modify a healthy environment with good categories is 63.1%, and good categories of public health facilities is53.84%. Respondents who experienced a smear (+) is equal to 69.23% and smear (-) of 30.77%. Familydutiesgood category is 47,7% and not good categoriesis 52,3%. A total of 31 people with family duties good thereare 12 people suffered smear (+).Conclusion: There is no significant relationship between family duties with pulmonary TB incidence in PuskesmasPerumnas II Pontianak in 2014 (p = 0.158).Keywords: Tuberculosis, Family Duties* Nursing Student of Tanjungpura University** Nursing Lecturer of Tanjungpura University